Bulletin of the International Council of Social Democratic Women. - International Council of Social Democratic Women (ICSDW) (London : ICSDW, 1955)
Bibliotheek Camille Huysmans
Engels
Periodiek
Keywords: Socialistische Internationale (1951- ).; socialistische vrouwenbeweging